Assessing performance validity with the TOMM and automatized sequences task in a pediatric psychiatric inpatient setting. Issue 6 (17th August 2020) - Weber Ku, Elyssa; Oliveira, Jane S.; Cook, Nathan E.; McCurdy, Kyle; Kavanaugh, Brian; Cancilliere, Mary Kathryn; Holler, Karen A.
ABSTRACT: This study examined the performance of children consecutively admitted to an inpatient psychiatric unit on the Test of Memory Malingering (TOMM) (aged 5–12; n = 96) and Automatized Sequences Task (aged 8–12; n = 67). Eighty-three percent of children passed the TOMM Trial 2 ( M raw score = 47.7, SD = 4.7) and 76% of children passed the Automatized Sequences Task total time ( M = 23.1 seconds; SD = 8.2). The concordance rate between the TOMM and the total time on the Automatized Sequences Task was 73.1%. Receiver operating characteristic curves indicated that of the Automatized Sequences Task subtests, only Counting 1–20 significantly differentiated children who passed Trial 2 of the TOMM from those who did not pass Trial 2 of the TOMM (area under the curve = .756, p = .006). Performance on both PVTs was unrelated to demographic characteristics and measures of psychological and neuropsychological functioning on both the TOMM and Automatized Sequences Task. Further research is needed to determine whether the nearly 1 in 4 children (23.9%) who performed below recommended cutoffs on Automatized Sequences Task reflects genuine suboptimal effort, cognitive difficulties among these children, and/or other factors.